Fostering Cultures of Sustainability in a Multi-Unit Office Building: A Theory of Change - Dreyer, Bianca Christel; Riemer, Manuel; Spadafore, Brittany; Marcus, Joel; Fernandes, Devon; Taylor, Allan; Whitney, Stephanie; Geobey, Sean; Dennett, Aisling (Frontiers in Psychology, 2021)
Psychological approaches to fostering sustainability are heavily focused on individual behaviours and often insufficiently address the physical and social contexts individuals are embedded in. This limits the ability to create meaningful long-lasting change as many of day-to-day behaviours are social practices embedded in broader cultural norms and systems. This is particularly true in the work context, where organizational cultures heavily condition both the actions of individual employees and the collective actions of organizations. Thus, we argue cultures, not behaviours, must become the focus of sustainability change efforts. In this paper we present a theory of change aimed at fostering strong organizational cultures of sustainability within a high-performance multi-tenant office building. Our theory takes a systems perspective that incorporates the social and physical aspects of the work environment, and views culture change as a co-creative exercise involving engagement of multiple stakeholders. The paper concludes with implications for practice and research.